What makes online political ads unacceptable? Interrogating public attitudes to inform regulatory responses - Junyan Zhu; Katharine Dommett; Tom Stafford (Humanities & Social Sciences Communications)
Abstract Online political advertising is often portrayed negatively, yet there is limited evidence regarding what exactly the public deems unacceptable. This paper provides new insights into public attitudes based on an online survey conducted in 2022, in which 1881 respondents evaluated political ads placed on Facebook during the 2019 UK General Election. We find that citizens do not inherently view political ads as unacceptable, and that perceptions of acceptability are influenced by partisan and demographic factors. We also find that ads deemed compliant with existing regulatory protocols for non-political advertising are considered more acceptable, suggesting a case for extending the existing regulatory regime to political ads. Delving deeper into our survey data, we explore the drivers behind these perceptions of acceptability and find that concerns about the content and tone of ads play a significant role. These findings provide valuable insights for those seeking to develop codes of conduct to govern practices in this space. Overall, our study offers a nuanced understanding of public attitudes toward online political advertising and identifies possible pathways for regulatory reform.